ИССЛЕДОВАНИЕ ВЛИЯНИЯ ТРАВЯНОГО ПОКРОВА НА ТЕМПЕРАТУРУ ГРУНТА ДЛЯ КРОВЕЛЬНОГО ОЗЕЛЕНЕНИЯ - Ткаченко, Татьяна; Милейковский, Виктор (My University, 2017)
Active development of modern cities has led to the problem of shortage of land, especially in the central urban areas. This has created serious environmental problems that can be solved with the help of roof greening. The work carried out to test the hypothesis of “cooling effect” vegetable green roof layer. Our experimental studies suggest that the “cooling effect grass” due to the evaporation of moisture during temperature measurement. We have identified the main thermal processes occurring in the top layer of the roof: the reflection and absorption of solar radiation, the thermal resistance between the soil and the surrounding air by conduction and convection, accumulation of heat in the soil, moisture exchange between the soil, the grass and the environment. Reducing the temperature of the grass compared to bituminous coating due to the decrease of the absorption of solar energy. Low soil temperature as compared with ambient air connected with the insulating properties of grass that saves “cold” accumulated during the night by ground.
STUDY ON EFFECT OF GRASS COVER ON GROUND TEMPERATURE OF GREEN ROOFS
BADANIE WPŁYWU POKRYWY TRAWIASTEJ NA TEMPERATURĘ GRUNTU NA DACHACH ZIELONYCH
DOI: 10.17512/bozpe.2017.1.10
Keywords: green roof; vegetation layer; cooling effect